2012
DOI: 10.3109/08941939.2012.697977
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Surgeon-Performed Gallbladder Ultrasound in Identification of Acute Cholecystitis

Abstract: Both SPUS and RPUS had a high accuracy rate in electing the acute cholecystitis. Our data support the fact that the use of US by general surgeons is effective in the diagnosis of acute cholecystitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 8 publications
0
12
1
1
Order By: Relevance
“…We demonstrate a lower sensitivity for detecting gallstones compared to some previous studies where sensitivities in the range of 95-100 % have been described [3,8,9,15]. These studies had a higher prevalence of gallstones in the study population, which together with clinically suspected biliary disease for the patients included could have led to selection bias, and an overestimation of the sensitivity.…”
Section: Discussioncontrasting
confidence: 61%
“…We demonstrate a lower sensitivity for detecting gallstones compared to some previous studies where sensitivities in the range of 95-100 % have been described [3,8,9,15]. These studies had a higher prevalence of gallstones in the study population, which together with clinically suspected biliary disease for the patients included could have led to selection bias, and an overestimation of the sensitivity.…”
Section: Discussioncontrasting
confidence: 61%
“…For example, studies of bedside ultrasound performed by surgeons in Sweden, Japan and Iran have reported sensitivities of 60%, 84.2% and 89.6% and specificities of 98.6%, 92.1% and 96.6%, respectively, for the imaging diagnosis of acute cholecystitis. [11][12][13] It is important to note that even formal ultrasound scan performed by experienced radiology staff is an imperfect test. A systematic review and meta-analysis comparing the diagnostic performance of radiological investigations for the imaging diagnosis of acute cholecystitis reported formal ultrasound to have a sensitivity of only 81% (95% CI 75-87) and specificity of 83% (95% CI 74-89).…”
Section: Discussionmentioning
confidence: 99%
“…However, other published studies of bedside ultrasound for acute cholecystitis have generally reported much lower sensitivities and specificities. For example, studies of bedside ultrasound performed by surgeons in Sweden, Japan and Iran have reported sensitivities of 60%, 84.2% and 89.6% and specificities of 98.6%, 92.1% and 96.6%, respectively, for the imaging diagnosis of acute cholecystitis 11–13 . It is important to note that even formal ultrasound scan performed by experienced radiology staff is an imperfect test.…”
Section: Discussionmentioning
confidence: 99%
“…4 Because of this, AC remains very much a clinical diagnosis, with US provid ing a diagnostic adjunct. 22 Additionally, many studies use a pathological diagnosis as the gold standard, which may not correlate with clinical findings. The literature is additionally limited by many singleinstitution, retro spective, small data sets.…”
Section: Discussionmentioning
confidence: 99%